Eagle i-Bot: an eye-controlled system - Md Khalilur, Rhaman; Meem, Mohona Gazi; Afrin, Onindita; Hassan, Md. Mahabub; Bhuiyan, Farazul Haque (© International Organization Of Scientific Research (IOSR), 2016)
This article was published in IOSR Journal of Computer Engineering (IOSRJCE) [© International Organization Of Scientific Research (IOSR)] and the definite version is available at: http://iosrjournals.org/iosr-jce/papers/Vol7-Issue2/D0722328.pdf?id=404 The article website is at: www.iosrjournals.org